Measuring real value and inflation - Claude Hillinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
The most important economic measures are monetary. They have many different names, are derived in different theories and employ different formulas. Yet, they all attempt to do basically the same thing: to separate a change in nominal value into a `real part' due to the changes in quantities and an inflation due to the changes of prices. Examples are: real national product and its components, the GNP deflator, the CPI, various measures related to consumer surplus, as well as the large number of formulas for price and quantity indexes that have been proposed. The theories that have been developed to derive these measures are largely unsatisfactory. The axiomatic theory of indexes does not make clear which economic problem a particular formula can be used to solve. The economic theories are for the most part based on unrealistic assumption. For example, the theory of the CPI is usually developed for a single consumer with homothetic preferences and then applied to a large aggregate of diverse consumers with non-homothetic preferences. In this paper I develop a unitary theory that can be used in all situations in which monetary measures have been used. The theory implies a uniquely optimal measure which turns out to be the Törnqvist index. I review, and partly re-interpret the derivations of this index in the literature and provide several new derivations. The paper also covers several related topics, particularly the presently unsatisfactory determination of the components of real GDP.
urn:nbn:de:bvb:19-epub-2090-5
Keywords: 330; consumer price index; consumer surplus; money metric; price and quantity indexes; welfare measurement; Verbraucherpreisindex; Inflation; Wohlfahrtsanalyse; Theorie